Implementation of chlorine dioxide disinfection: Effects of the treatment change on drinking water quality in a full-scale distribution system. Issue 5 (1st September 2002) - Volk, C J; Hofmann, R; Chauret, C; Gagnon, G A; Ranger, G; Andrews, R C
Abstract : Drinking water utilities may have to consider changing disinfectant to improve water quality and meet more stringent disinfection regulations. The objective of this study was to evaluate the response of a full-scale drinking water distribution system to a change in disinfectant from chlorine to chlorine dioxide, in terms of its impact on microbiological stability and disinfection by-product formation. Chlorine dioxide residuals were consistently present above detection limits throughout the distribution system (>0.20 mg/L). Over a study period of 3.5 months, no degradation of bacterial water quality occurred after implementing the new disinfectant. Chlorine dioxide maintained total bacteria (microscopic counts) and heterotrophic plate count levels below 2 x 10 5 cells/mL and 1000 CFU/mL, respectively. The change in disinfectant from chlorine to chlorine dioxide led to an 85% reduction in trihalomethanes (i.e., from 30 to 5 μμg/L) and a 60% reduction in haloacetic acids (i.e., from 20 to 8 μμg/L). Chlorine dioxide represents a valuable tool to produce high quality water and is a strong alternative to chlorine for certain distribution systems. Key words : distribution system, chlorine dioxide, drinking water quality, disinfection by-products.